Hurtar a los de casa: notas sobre hurtos domésticos - Ortego Gil, Pedro (Cuadernos de Historia del Derecho, 2011)
The domestic thefts appear between the most well-known thefts from the Roman period. This article examines the main characteristics that shaped content, included its religious connotations. The severity of the legal penalties favoured its inapplicability, allowing an increase of this inferior delinquency, punishing these facts, in the most part, within the private sphere.